P4_2 Visibility of the Great Fire of London - Brewster, Nicholas; Adams, Nathan; Smith, Jason; Kerr, Tendayi (Physics Special Topics, 2011)
<span style="font-size: 10pt; font-family: ";Calibri";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Great fire of London is investigated to determine whether it would have been visible from a satellite in both high and low Earth orbit, had such technology been available.Â  Both resolving power and radiated power are tested and it is found that the resolving power is more influential than that of radiative transfer.Â  In low Earth orbit the Great Fire would have been visible with the naked eye, but in geostationary orbit a camera with a large aperture would be required.